Analisis Faktor yang Berhubungan dengan Kinerja Perawat Pelaksana dalam Memberikan Asuhan Keperawatan - Ahmad, LB Jaenabun Habibillah; Budiman, Budiman; Inayah, Iin; Mulyati, Mulyati; Rohayani, Lilis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze factors related to nurse performance at Annisa Hospital, Bekasi Regency. This study used an associative research design with a cross-sectional approach. The results showed a significant relationship between motivation and nurse performance (Sig. 0.013). Exp(B) 2.39. The relationship between competence and performance was very significant (Sig. 0.0001). Exp(B) 120.09. There was a very significant relationship between work facilities and nurse performance (Sig. 0.001). Exp(B) 3.33. The relationship between work culture and performance was very significant (Sig. 0.0001). Exp(B) 25.43. The relationship between leadership and performance was very significant (Sig. 0.0001). Exp(B) 346.2. The relationship between discipline and performance was very significant (Sig. 0.0001). Exp(B) 58.89. In conclusion, motivation, competence, work facilities, work culture, leadership, and discipline have a positive and significant relationship to nurse performance at Annisa Hospital, Bekasi Regency. Leadership is the most dominant factor, followed by discipline and work culture. Keywords: Nurse Performance, Nursing Services, Hospital